Protection of Citizens’ Constitutional Rights in the Digital Era - Gunawan, Mohamad Sigit; Santos, Luis; Flores, Josefa (Rechtsnormen: Journal of Law, 2025)
Background: The digital era has brought about significant advancements in technology, leading to an increased reliance on digital platforms for communication, transactions, and daily activities. While these technological advancements provide numerous benefits, they also raise concerns about the protection of citizens’ constitutional rights, particularly in terms of privacy, freedom of expression, and data security. Governments and legal systems face the challenge of ensuring that constitutional rights are upheld in an increasingly digital society, where the lines between public and private spheres are often blurred. Objective: This study aims to examine the protection of citizens’ constitutional rights in the digital era, focusing on the balance between technological innovation and individual rights. The research seeks to assess the effectiveness of existing legal frameworks in safeguarding privacy, freedom of speech, and other fundamental rights in the context of the digital landscape. Method: A qualitative research design was used, employing case studies, legal analysis, and interviews with legal professionals, policymakers, and technology experts. The data collected was analyzed to evaluate how well constitutional rights are protected in digital environments and to identify potential gaps in legal protection. Results: The findings indicate that while there are legal frameworks in place to protect constitutional rights, there are significant challenges in keeping pace with technological advancements. Privacy violations, surveillance concerns, and data breaches were highlighted as key issues. Conclusion: The study concludes that existing legal protections must be adapted to address the challenges posed by the digital era, with a focus on strengthening privacy laws, improving data security, and ensuring accountability in digital platforms.